Moderate Mitral Regurgitation and Coronary Disease: Treatment with Coronary Bypass Alone? - Hakimeh Sadeghian; Abbassali Karimi; Hosein Ahmadi; Mojtaba Salarifar; Saeed Sadeghian; Nader Fallah; Navid Paydari; Mohammad Majd (Journal of Tehran University Heart Center, 2006)
Background: In cases of moderate(2 or 3+ on a scale of 0 to 4+) nonorganic mitral regurgitation (MR) and coronary artery disease, operative strategy continues to be debated between coronary artery bypass grafting alone (CABG) or concomitant valve repair. To clarify the optimal management of these patients, we evaluated the mid-term results of isolated CABG in the study group. Methods: From March 2002 to February 2005, 40 consecutive patients (57.5% male, mean age: 62.45±8.7 years, mean ejection fraction: 44.15±12.6%, mean New York Heart Association class 2.5±0.78) with coronary artery disease and moderate MR without organic mitral valve disease (prolapse, rheumatism, etc.) underwent CABG alone. Thirty one (77.5%) patients had either postoperative or follow-up transthoracic echocardiography with mean follow up time of 10.82±8.12 months. Patient's pre and postoperative data were compared to evaluate the results of isolated CABG on moderate MR. Results: MR was ischemic (with persistent wall motion abnormality) in 25(62.5%) patients and functional (without persistent wall motion abnormality) in 15(31.5%). Considering postoperative and follow up transthoracic echocardiography, 54.8% had no or mild MR (29% MR 1+, 25.8% no MR) and 45.2% had moderate MR (16.1% MR 3+, 29% MR 2+). Resolution of MR was significant (p<0.001), but it had no correlation with ischemic MR (p=0.46), preoperative ejection fraction (p=0.09), LV systolic (p=0.70) and diastolic dimensions (p=0.80). Seven patients died, 2 in hospital and 5 later. Conclusion: Although for coronary artery disease accompanying moderate nonorganic MR, CABG alone reduces severity of MR significantly, many patients are left with moderate MR. Preoperative diagnosis of moderate nonorganic MR may warrant concomitant mitral repair.